KUALITAS JASA DAN KEPUASAN NASABAH - Sofyan, Sofyan (Universitas Riau, 2016)
Service Quality and Customer Satisfaction. As one of the companies engaged in service,PT. Bank Syariah Mandiri Cabang Dumai active role in serving its customers. The emergence ofcomplaints and complaints from customers, is one form of customer dissatisfaction against the company.This makes the researcher is interested to discuss how the influence of service quality on customersatisfaction at PT. Bank Syariah Mandiri Cabang Dumai. The data were analyzed by product moment,a simple linear regression and significance testing, and performed using SPSS version 17 for Windows.Data collection techniques used are questionnaires and interviews. The study was conducted bytaking the respondents using incidental sampling technique by 138 people. Based on test validity andreliability of all the data is valid. Based on the results of analysis product moment that the author didwith the number of 138 respondents and the level of 5% error rate relationship between the variablesof service quality with variable customer satisfaction is very strong. For a simple linear regressionanalysis, the regression coefficient of service quality in this equation was obtained for 0.684 (positive)which means that if the scores on the variables of service quality increases, customer satisfaction willincrease by 0.684. And the significance test the influence of service quality on customer satisfaction,For t <0.05 then H0 rejected and Ha accepted otherwise. So it can be concluded that the variablequality of services have a significant effect on customer satisfaction.